Recurrent transient global amnesia at high altitude - Bucuk, M.; Tomic, Z.; Tuskan-Mohar, L.; Bonifacic, D.; Bralic, M.; Jurjevic, A. (High Altitude Medicine & Biology, 2008)
We report the case of a 57-year-old man who experienced recurrent episodes of memory loss that resemble transient global amnesia (TGA). The first episode lasted 20 minutes, and the second was 8 hours long.